2015
DOI: 10.5455/ijmsph.2015.27112014153
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of ABO and Rh blood groups in patients with tuberculosis in Rohilkhand region of Uttar Pradesh

Abstract: among millions of people each year and ranks as the second leading cause of death from an infectious disease worldwide, after the human immunodeficiency virus. According to latest estimates, over 8.6 million new TB cases were seen in 2012 and a whooping 1.3 million deaths due to TB in the world. The number of deaths due to TB is unacceptably large given that most are preventable. [1] Among the various factors that contribute to a person's individuality are antigens that are attached to the surface of red blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In the available literature, the association between blood group and various infectious diseases such as plague, anthrax, cholera, smallpox was reported [13][14][15][16]. Similarly, blood groups and PT correlation studies are also available [4,17,18]. In a study by Rao et al, the authors reported significant association between A blood group and PT; the authors reported that among PT cases 18% PT patients were A+ and non of the participants were A- [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the available literature, the association between blood group and various infectious diseases such as plague, anthrax, cholera, smallpox was reported [13][14][15][16]. Similarly, blood groups and PT correlation studies are also available [4,17,18]. In a study by Rao et al, the authors reported significant association between A blood group and PT; the authors reported that among PT cases 18% PT patients were A+ and non of the participants were A- [17].…”
Section: Discussionmentioning
confidence: 99%
“…Various Factors such as quality, quantity of sputum, number of samples, staining technique used, gender and so on influence smear microscopy results [3]. Similarly, proteins present on the surface of the red blood cells (RBC) as well as the serum immunoglobulins influence the persons individuality [4].…”
Section: Introductionmentioning
confidence: 99%